Upaya Meningkatkan Teknik Dasar Long Service Bulutangkis Melalui Metode Drill Pada Siswa Sekolah Dasar - Heri Setiawan, Ryan; Nurhidayat , Nurhidayat; Nur Warthadi, Anugrah (Universitas Hamzanwadi, 2024)
The problem in this study is the low understanding of students in mastering basic badminton techniques, the lack of maximum students in doing long service, the lack of student learning concentration which has an impact on learning outcomes. The purpose of this study was to improve the basic techniques of badminton long service through the drill method in elementary school students. This research method is a class action research method carried out in 2 cycles, where each cycle consists of three meetings. The research subjects were grade V students of SDN 2 Gunan totaling 10 students consisting of 6 boys and 4 girls. Data collection was done through observation and tests. Data analysis was done descriptively quantitative. The results of the study were that in the pre-cycle there were only 2 students who could perform basic long service techniques in the good category. In cycle I there were 1 student in the very good category, 2 students in the good category, 2 students in the sufficient category, 5 students were not complete in performing basic long service techniques. In cycle II there were 2 students in the very good category, 4 students in the good category, 3 students in the sufficient category, 1 student was not complete in performing basic long service techniques. This conclusion shows that the drill method is able to improve basic long service techniques in elementary school students.